A study of safety, range, usefulness and satisfaction of New Energy Vehicle (NEV) amongst Gen Y in Shenzhen City, China / Mohd Haniff Jedin and Li Jialin - Jedin, Mohd Haniff; Li, Jialin (Universiti Teknologi MARA, Perak, 2023)
In China, new energy vehicles (NEVs) are becoming more important as a solution against the environmental and energy crisis. This phenomenon is also an advantage to reduce petrol cost and more economic sustainability. Subsequently, this paper attempts to examine the elements of satisfaction amongst the Gen Y who owned and experienced driving NEV. DOI theory is used as a foundation in this study. A survey of 394 NEV drivers in the City of Shenzhen was used in the analysis. As a result, all the three variables were found to be significant to influence the experience in driving NEV. In addition, the findings of this research may provide some insight and useful information for the government and related agencies, NEV manufacturers, and academic researchers.